Assessing ethical climates in critical care and their impact on patient outcomes. Issue 1 (March 2019) - Okenyi, Emmanuel; Donaldson, Thomas Michael; Collins, Andrea; Morton, Ben; Obasi, Angela
Intensive care services are defined as "a multidisciplinary and interprofessional specialty dedicated to the comprehensive management of patients having, or at risk of developing, acute, life-threatening organ dysfunction" [1]. They play a vital role in modern healthcare in supporting the sickest patients to improve survival. For patients at the highest risk of death, ethical dilemmas concerning the benefits and harms of persisting with potentially futile treatment can arise. A recent study by Benoit et al . [2] examined how the quality of the "ethical climate" may affect the predictive value of clinician agreement on excessive levels of treatment. They hypothesised that concordant perceptions of excessive care in better ethical climates would be more predictive of patient outcomes at 1 year and would be associated with shorter time intervals between care perceptions and treatment-limitation decisions or death. Intensive care units with a "good" ethical environment are more likely to identify perceived excessive patient care. Patients with perceived excessive care were more likely to die and time to death was shorter in units with a "good" ethical environment. http://ow.ly/vnFP30neAZN